Amphiphilic block polymer-based self-assembly of high payload nanoparticles for efficient combinatorial chemo-photodynamic therapy. (1st January 2020) - Ma, Qisan; Zhao, Yanna; Guan, Qingran; Zhao, Yuping; Zhang, Huaizhen; Ding, Zhuang; Wang, Qingpeng; Wu, Yushu; Liu, Min; Han, Jun
Abstract: Combinatorial chemo-photodynamic therapy is regared as effective cancer therapy strategy, which could be realized via multiple nano-drug delivery system. Herein, novel high payload nanoparticles stabilized by amphiphilic block polymer cholesterol- b -poly(ethylene glycol) (PEG)2000 (Chol-PEG2000 ) were fabricated for loading chemotherapeutic drug 10-hydroxycamptothecin (HCPT) and photosensitizer chlorin e6 (Ce6). The obtained HCPT/Ce6 NPs showed uniform rod-like morphology with a hydration diameter of 178.9 ± 4.0 nm and excellent stability in aqueous solution. HCPT and Ce6 in the NPs displayed differential release profile, which was benefit for preferentially exerting the photodynamic effect and subsequently enhancing the sensitivity of the cells to HCPT. Under laser irradiation, the NPs demonstrated fantastic in vitro and in vivo anticancer efficiency due to combinational chemo-photodynamic therapy, enhanced cellular uptake effectiveness, and superb intracellular ROS productivity. Besides, the NPs were proved as absent of systemic toxicity. In summary, this nanoparticle delivery system could be hopefully utilized as effective cancer therapy strategy for synergistically exerting combined chemo-photodynamic therapy in clinic. Graphical Abstract: UF0001